Electrospinning pure protein solutions in core-shell fibers - Tiwari, Sandeep Kumar (2013)
Electrospinning of protein-loaded fibers faces many challenges, e.g. burst release owing to segregation of the protein on the fiber surface, loss of activity due to electrospinning conditions, limitation of loading capacity etc. Core–shell electrospinning provides an effective way to electrospin fibers wherein the core can be loaded with bioactive molecules in friendly conditions of a compatible polymer solution, thereby protecting the molecules from the electrostatic field and organic solvent of shell solutions. The shell polymer, after the electrospinning, acts as a barrier to control the release of the loaded molecules. However, the limitation of loading capacity still remains due the prerequisite of using an additional polymer as additive to achieve the minimum viscosity of the core solution required for viscous drag by the shell solution being drawn by the electrostatic force. The work reported here aims to alleviate the need of a polymer additive by using aqueous protein solutions of very high concentration. High concentrations of protein solutions were successfully electrospun as the core of the protein–poly(lactide-co-glycolic acid) core–shell fibers. A partitioning effect was seen in the controlled release of hydrophilic proteins as they were retained in the aqueous core for longer times. Using lysozyme as a model protein, it was shown that the activity is significantly retained after electrospinning, compared with electrospinning in monolithic fibers. Moreover, the lysozyme activity was also comparable with the lysozyme released from core–shell fibers spun using poly(vinyl acetate) as additive in the core.